STRATEGI KEPOLISIAN SEKTOR PERANAP DALAM MENANGANI KASUS PENAMBANGAN EMAS ILEGAL PETI DI KECAMATAN PERANAP (Studi Kasus Pada Polsek Peranap) - Setiadi, Melki; Sobri (UIR PRESS, 2022)
Riau Province is one of the provinces that contributes to oil and gold mining in Indonesia. As has been done by the people of Indragiri Hulu Regency, Peranap District, where some of the people carry out mining activities for mineral resources (gold) as a livelihood. Because some of these activities are carried out illegally, it raises pros and cons and gets a reaction from law enforcement officers, namely the police. The research method is qualitative because the research data is more relevant and more likely to interpret the data found in the field, so the researcher determines that this research research can be directed to collect data, take meaning and gain understanding of the problems found. There were five resource persons in this study. The purpose of this study was to find out how the strategy of the Peranap police sector against illegal gold mining in Peranap District. To solve the problem in this research, the theory of reality of social crime is used. The results of data analysis using purposive techniques. Based on the results of the study that the phenomenon of crime in the act of gold mining, namely that which is carried out by the community does not have a permit that is in accordance with the rules in accordance with the rules of the government. So the mining activity is considered illegal (crime).